Characterizing the Spectrum of Latent Mycobacterium tuberculosis in the Cynomolgus Macaque Model: Clinical, Immunologic, and Imaging Features of Evolution. (6th January 2023) - Medrano, Jessica Marie; Maiello, Pauline; Rutledge, Tara; Tomko, Jaime; Rodgers, Mark A; Fillmore, Daniel; Frye, L James; Janssen, Christopher; Klein, Edwin; Flynn, JoAnne L; Lin, Philana Ling
Abstract: Mycobacterium tuberculosis infection outcomes have been described as active tuberculosis or latent infection but a spectrum of outcomes is now recognized. We used a nonhuman primate model, which recapitulates human infection, to characterize the clinical, microbiologic, and radiographic patterns associated with developing latent M. tuberculosis infection. Four patterns were identified. "Controllers" had normal erythrocyte sedimentation rate (ESR) without M. tuberculosis growth in bronchoalveolar lavage or gastric aspirate (BAL/GA). "Early subclinicals" showed transient ESR elevation and/or M. tuberculosis growth on BAL/GA for 60 days postinfection, "mid subclinicals" were positive for 90 days, and "late subclinicals" were positive intermittently, despite the absence of clinical disease. Variability was noted regarding granuloma formation, lung/lymph node metabolic activity, lung/lymph node bacterial burden, gross pathology, and extrapulmonary disease. Like human M. tuberculosis infection, this highlights the heterogeneity associated with the establishment of latent infection, underscoring the need to understand the clinical spectrum and risk factors associated with severe disease. Abstract : Mycobacterium tuberculosis infection outcomes are a spectrum between active disease and latent infection. We used a nonhuman primate model to identify patterns of latency based on serial clinical, microbiological, and imaging data to characterize the variability in latent infection evolution.